The performance of fire wood stove for heat exchanger tubeless type in the fluidized bed dryer of orthodox black tea - Abbas, Tajudin (Research Institute for Tea and Cinchona, 2013)
The biomass potential of tea plantations such as tea pruning waste, shade tree waste and waste of tea replanting are large enough. Energy derived from biomass is a renewable energy source that environmentally friendly, and it does not cause a negative impact to the environment. Heat exchanger tubeless type can only use fossil fuel. To replace the fuel derived from biomass on the tubeless type of heat exchanger, the furnace must be designed specifically as a substitute for fuel oil burner. This paper provides the result of engineering design of tubeless type heat exchanger of and their performance in a fluidized bed dryer of orthodox black tea. Apart from that, the design suitable also for the green tea drying machines. As a substitute for fuel oil burner, the heat exchanger tubeless type can use waste of tea replanting. The ratio of fire wood was 0.90 kg per kilogram of made tea with 57.9% of the energy efficiency and 46.3% of drying energy efficiency.